2016
DOI: 10.1097/icl.0000000000000170
|View full text |Cite
|
Sign up to set email alerts
|

Contact Lens Applications and the Corneal Dystrophies

Abstract: The cornea is precious to sight. Its intricate cellular arrangement and physiology enable it to be transparent and refractive. Corneal dystrophies (CDs) impact vision at various decades of life depending on the dystrophy at hand. Left untreated, visual ramifications ensue. This review article will summarize the current knowledge of the various CDs and the relatively controversial classification based on new genetic knowledge and clinical and histological characteristics. The application of contact lenses, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
2
0
2
Order By: Relevance
“…There are some cases in which fitting a contact lens can slow the condition or aid resolution of symptomatic episode. The current knowledge in the field reviewed providing insight into each corneal dystrophy and the methods and rationale for contact lens management [374]. Most evidence, such as for Meesmann corneal dystrophy [375], are only from case reports.…”
Section: Corneal Dystrophy -Reis-buckler Meesmann Epithelial Basement Membrane Dystrophy and Othersmentioning
confidence: 99%
“…There are some cases in which fitting a contact lens can slow the condition or aid resolution of symptomatic episode. The current knowledge in the field reviewed providing insight into each corneal dystrophy and the methods and rationale for contact lens management [374]. Most evidence, such as for Meesmann corneal dystrophy [375], are only from case reports.…”
Section: Corneal Dystrophy -Reis-buckler Meesmann Epithelial Basement Membrane Dystrophy and Othersmentioning
confidence: 99%
“…Neben den hier besprochenen operativen Herangehensweisen kommen auch (weiche und harte) Kontaktlinsen bei Patienten mit verschiedenen Hornhautdystrophien zum Einsatz. Neben einer Reduktion von Schmerzen und Beschwerden durch die alterierte Hornhautoberfläche kann mit Kontaktlinsen auch ein durch die Dystrophie induzierter (größtenteils irregulärer) Astigmatismus (teil-)korrigiert werden und so eine Visusverbesserung erreicht werden [16]. Auch wird die postoperative Versorgung mit Kontaktlinsen zur Rezidivprophylaxe diskutiert.…”
Section: Behandlung Epithelialer Und Stromaler Hornhaut Dystrophien Munclassified
“…Dadurch sollen die Epithelzellen weniger lange auf der Hornhautoberfläche verbleiben und könnten somit auch weniger degeneratives Material produzieren, sodass weniger Ablagerungen im Hornhautstroma zu erwarten wären. Ob und in welchem Maße der regelhafte Gebrauch von Kontaktlinsen die Progression einer Dystrophie beeinflussen könnte, ist aber nach wie vor nicht geklärt [16].…”
Section: Behandlung Epithelialer Und Stromaler Hornhaut Dystrophien Munclassified
“…RGP lenses have the benefit of masking corneal irregularities, thus providing a regular anterior refractive surface [10]. erefore, they have been also successfully used to treat other corneal ectasias, including irregular corneas following photorefractive surgery, penetrating keratoplasty, and corneal dystrophies [10][11][12]. Comparative studies demonstrated that specialty design contact lenses, new design scleral lenses, and hybrid lenses have better patients' comfort [8] levels than that by conventional RGP lenses [13].…”
Section: Introductionmentioning
confidence: 99%